ASSOCIATION BETWEEN TOBACCO USE AND BEHAVIOURAL PROBLEMS AMONG ADOLESCENTS. - Shabnam Sayyad, Pooja Kasturkar, Jaya Gawai, Dr. Manoj Patil (International Journal of Modern Agriculture, 2020)
Background: Many studies have documented results relating to the correlation between tobacco use and emotional / behavioral disorders, some study has examined this correlation after searching for potential variables that have been shown to be strongly associated with both tobacco use and emotional / behavioral issues and may have a direct impact on the association with mental health of adolescents and tobacco use. Aim: goal of this study is to assess the correlation between smoking and behavioural problems among adolescents. Objective: to identify tobacco use habit among adolescence, behavioural problems among adolescence, association between tobacco use and behavioural problem among adolescence, to associate the tobacco use score among adolescence with their demographic variables, associate the behavioural problem score among adolescence with their demographic variables. Methodology: It is a cross sectional study and adolescence are the participants of this study. The adolescence will be selected as per inclusion and exclusion criteria and sampling technique will be selected as purposive sampling technique. Data will be collected by demographic variables of participants and checklist will be used for tobacco use of participants and behavioural problems will be assessed by modified behavioural scale. Behavioural problems scale (Strengths and Difficulties Questionnaire) distributed for tobacco use of participants and behavioural problems for that required 30 minutes to each participants. Results: There may be much association between tobacco use and behavioural problem among adolescence and this association will be tested with demographic variables by regression analysis. Conclusion- Conclusion will be drawn from the statistical analysis.